Pengaruh Transparansi Publik Dan Kompetensi Terhadap Kualitas Pelayanan Publik Yang Dimediasi Oleh Kinerja Aparatur (Studi Pada Kecamatan Karang Penang Kabupaten Sampang) - Moh. Faruk; Hadi Susanto; Sri Mulyani (Journal of Management and Creative Business, 2023)
Moh. Faruk, 2023. The Effect of Public Transparency and Competence on the Quality of Public Services Mediated by Apparatus Performance (Study in Karang Penang District, Sampang Regency). Wijaya Putra University Postgraduate Program in Surabaya. This type of research is in the type of cross-sectional research, the approach used is a quantitative approach with a total sample of 42 people. The aims of this study were 1) to describe public transparency, competence, apparatus performance and quality of public services in Karang Penang District, Sampang Regency. 2) To test and analyze public transparency has a significant influence on the quality of public service apparatus of the Karang Penang District, Sampang Regency. 3) To test and analyze public transparency, it has a significant influence on the performance of the Karang Penang District apparatus, Sampang Regency. 4) To test and analyze competence has a significant influence on the quality of public service apparatus of the Karang Penang District, Sampang Regency. 5) To test and analyze competence, it has a significant influence on the performance of apparatus in the Karang Penang District, Sampang Regency. 6) To test and analyze the performance of apparatus that has a significant influence on the quality of public services in Karang Penang District, Sampang Regency. 7) To test and analyze public transparency, it has a significant influence on the quality of public service apparatus of the Karang Penang District apparatus, Sampang Regency, which is mediated by the performance of the apparatus. 8) To test and analyze competence, it has a significant influence on the quality of public service apparatus of the Karang Penang Subdistrict, Sampang Regency which is mediated by the performance of the apparatus.The results showed that: 1) Public transparency has a positive effect on the quality of public services in Karang Penang District, Sampang Regency with an original sample value of 0.311. 2) Public transparency has a positive effect on the performance of apparatus in Karang Penang District, Sampang Regency with an original sample value of 0.563. 3) Competence has a positive effect on the quality of public services in Karang Penang District, Sampang Regency with an original sample value of 0.098. 4) Competence has a positive effect on the performance of apparatus in Karang Penang District, Sampang Regency with an original sample value of 0.304. 5) Apparatus performance has a positive effect on the quality of public services in Karang Penang District, Sampang Regency with an original sample value of 0.328. 6) Public transparency has a positive effect on the quality of public services which is mediated by the performance of the apparatus of the Karang Penang District, Sampang Regency with an original sample value of 0.185. 7) Competence has a positive effect on the quality of public services which is mediated by the performance of apparatus in Karang Penang District, Sampang Regency with an original sample value of 0.100.